Sergeant Ngorongo - Adeliyi Theophilus (Literamed Publications Ltd, 2009)
Termites are diligent and highly organized social insects. In this exciting story, Sergeant Ngorongo narrates how he and other termite soldiers are able to defend their castle against enemy attacks in three great battles.
Keywords: Juvenile Fiction / Adventure / Animal